The ivory thought : essays on Al Purdy - Lynch, Gerald, 1953-; Ganz, Shoshannah, 1976-; Kealey, Josephene T. M., 1980- (Re-appraisals, Canadian writers, 2008)
If one poet can be said to be the Canadian poet, that poet is Al Purdy (1918-2000). Numerous eminent scholars and writers have attested to this pre-eminent status. George Bowering described him as "the world's most Canadian poet" (1970), while Sam Solecki titled his book-length study of Purdy The Last Canadian Poet (1999). In The Ivory Thought: Essays on Al Purdy, a group of seventeen scholars, critics, writers, and educators appraise and reappraise Purdy's contribution to English literature. They explore Purdy's continuing significance to contemporary writers; the life he dedicated to literat